PEMETAAN KESESUAIAN PEMANFAATAN LAHAN PERKEBUNAN SAWIT (STUDI KASUS : KAB. SOLOK SELATAN, SUMATERA BARAT) - Defwaldi Defwaldi (Ensiklopedia of Journal, 2022)
Indonesia is known as an agricultural country because most of the people's livelihood as farmers. The use of land for agriculture and plantations in a sustainable manner requires development planning based on complete data and information regarding the condition, quality and characteristics of the land. How to anticipate the occurrence of mismatches in the use of agricultural and plantation land with the type of plant can be done by determining the plantation land with a predetermined designation so that there are no errors in its use. The purpose of this study was to analyze the suitability of land use for oil palm plantations with soil conditions in South Solok Regency. The availability of spatial information is one of the supporting data in realizing the land use resilience program. Utilization of remote sensing is one way to obtain land spatial information. The method used in this research is land surface temperature, inverse distance weighted, slope and overlay methods. The data used in this study are rainfall data in 2020, Landsat 8 Oli Imagery Data, Shuttle Radar Topography Mission data and soil type data. Analysis of the data in the study carried out overlay techniques on mapping the suitability of land use for oil palm plantations in South Solok Regency. The results of this study indicate that the suitable land (S2) with an area of 68,049, 23 Ha, Fairly Appropriate (S3) with an area of 55,144.91 Ha and Unsuitable (N) with an area of 235,707, 46 Ha for oil palm plantations in South Solok Regency.